UJI FITOKIMIA UNTUK MENGETAHUI KANDUNGAN SENYAWA ORGANIK PADA AKAR, DAUN, DAN BATANG TUMBUHAN SENGGUGU (Clerodendron serratum Spreng) - Emilia, Ita; Wahyudi, Agus (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2009)
ABSTRACTHas been studied, entitled "Knowing the Ingredients Test Phytochemicals for Organic Compounds in Roots, Leaves, and Stem Plants Senggugu (Clerodendron serratum Spreng) held in August until November 2006 at the Laboratory of Organic Chemistry, UNSRI Inderalaya. The purpose of this study was to determine the class of organic compounds contained in the roots, leaves, and stems of plants senggugu. The result is at the root, leaves and stems of plants senggugu (Clerodendron serratum Spreng) alkaloids contained organic compounds and classes of organic compoundclasses terpenoida flavonoida whereas none of the three parts of the plant. Special sections of leaves and stems of plants there are classes of organic compounds terpenoid types of steroids.Key words: Phytochemicals test, Clerodendron serratum, alkaloids, falvonoida, terpenoida.